Why does the Buddha support the 'all-existing'? Investigating scriptural proofs for the Sarvāstivāda school's 'all-existing' doctrine through the perspectives in the Saṃyukta Āgama and Vijñānakāya. - Xin 辛放, Fang (Asian Philosophy, 2025)
This article argues that tahe Sarvāstivāda School's foundational doctrine of 'all-existence' is posited as an axiom rather than a proposition requiring illation. The Āgamas exclusively possess the capacity to expound upon this doctrine. This article examines two scriptural proofs presented in the Abhidharmakośabhāṣya that substantiate the doctrine of 'the existence of the three times'. It argues for an inherent relationship between these proofs and highlights the Vijñānakāya exposition on 'the existence of the three times'. By scrutinizing the process of establishing 'the existence of the three times' in the Vijñānakāya, it becomes evident that its characterization of the right observation aligns closely with that of the Saṃyukta Āgama. As a result, the sūtras related to the right observation, including the inaugural sūtra of the Saṃyukta Āgama, serve as scriptural proofs for the Sarvāstivāda school's 'all-existing' theory.